2015
DOI: 10.1371/journal.pone.0130317
|View full text |Cite
|
Sign up to set email alerts
|

LPS Down-Regulates Specificity Protein 1 Activity by Activating NF-κB Pathway in Endotoxemic Mice

Abstract: BackgroundSpecificity protein (Sp) 1 mediates the transcription of a large number of constitutive genes encoding physiological mediators. NF-κB mediates the expression of hundreds of inducible genes encoding pathological mediators. Crosstalk between Sp1 and NF-κB pathways could be pathophysiologically significant, but has not been studied. This study examined the crosstalk between the two pathways and defined the role of NF-κB signaling in LPS-induced down-regulation of Sp1 activity.Methods and Main FindingsCh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 63 publications
0
15
1
Order By: Relevance
“…These gene products play vital roles in many physiological processes, in tissue repair and anti‐inflammatory responses. It has been confirmed that Sp1 is a direct target of miR‐21 in human smooth muscle cells and HEK293 cell lines . These findings collectively suggest that Sp1 may be a candidate target gene of miR‐21 in mouse cells.…”
Section: Discussionmentioning
confidence: 68%
“…These gene products play vital roles in many physiological processes, in tissue repair and anti‐inflammatory responses. It has been confirmed that Sp1 is a direct target of miR‐21 in human smooth muscle cells and HEK293 cell lines . These findings collectively suggest that Sp1 may be a candidate target gene of miR‐21 in mouse cells.…”
Section: Discussionmentioning
confidence: 68%
“…Our results revealed that LPS stimulation resulted in the upregulated expressions of in ammatory transcription factors, such as NF-κB [26], AP-1 [27], and Sp1-2 [28]. In addition, LPS increased IL-6 and its promoter activity.…”
Section: Discussionmentioning
confidence: 60%
“…Our results showed that LPS stimulation resulted in up-regulated expressions of inflammatory transcription factors such as NF-κB [26], AP-1 [27] and Sp1-2 [28].…”
Section: Discussionmentioning
confidence: 96%
“…Lower shows the promoter activities of mutant GR sites. Among them, mutant GR2 binding site showed a significant decrease compared with other mutant28 binding sites.…”
mentioning
confidence: 94%